Apakah Infrastruktur Jalan Mempengaruhi Ekspor? Pendekatan Vector Autoregressive - Khairul Amri (Inovbiz: Jurnal Inovasi Bisnis, 2019)
This study aims to investigate the effect of road infrastructure on exports for the case of the Indonesian economy. Using time-series data during the 1987-2013 period sourced from the Indonesian Bureau of Statistics (BPS), the econometric model employed pertain to Johanson co-integration test, vector autoregressive, and Granger causality test. The finding of the study points out that there is no long-term relationship between the two variables. The rising in exports positively and significantly was affected by road infrastructure three years earlier. Furthermore, export has a positive and significant effect on road infrastructure at a lag of 1. The increase in export commodities leads to the government to improve road infrastructure at the one-year horizon. The result of the Granger causality test indicates that there is a bidirectional causality relationship between exports and road infrastructure. The increase in road infrastructure led to an increase in exports, and the increase in exports also led to an increase in road infrastructure